A Study on Digital Signature Authentication Algorithm Based on Multi-Factor and Public Key Infrastructure - Park, Yoon-Jae; Lim, Yong-Hoon; Chae, Myung-Sin (International Journal of Engineering and Technology, 2019)
Today most people have connected each other with information communications technology (ICT) under Internet of Things (IOT) environment. It is not awkward to have more interactions with someone they never knew. The security has become very critical in IT systems, for the security most of services rely solely on password-based authentication that has made little technological progress over past decades. The password-based authentication is exposed directly to security vulnerabilities in IOT environment, thus leading to constant increase in security incidents. The research developed an innovative authentication method, called PASSCON, as a new digital signature authentication algorithm. It explains the algorism and explain why its users would feel comfortable and secure by using it. It also suggestion proof to verify its effectiveness. It does not use text-based authentication, which causes security flaw in password-based authentication. It works only on the userâ€™s dashboard. This can block SQL Injection Attack or Brute Force Dictionary Attack.Â In addition, the digital ink is used only on the specified device.Â It also prevents other device from generating an electronic signature even if it is a correct icon key. That is, even if the key of the userâ€™s information is leaked, the user's account is protectedÂ Â Â